The intelligent, responsive leader - Katz, Steven (College teacher); Dack, Lisa A.; Malloy, John Patrick (Thousand Oaks : Corwin, 2018)
Jump start your roles as'learning leader' and'lead learner!' Designed for leaders to learn and lead within the'middle space' between the seemingly opposing dynamics of district expectations and practitioner experience, this book advances the concept of the school as a learning organization. This innovative perspective guides leaders through an intentional, deliberate learning process to develop intelligent, responsive leadership practice. Using stories, strategies, and tools, the authors Explain the power of'purposeful practice' as a methodology for getting better Show how to build the requisite capacities to lead effectively via'influence' Describe how to turn adaptive challenges into leadership inquiries for growth'This important work demonstrates and reinforces the idea that continuous improvement can only come from deep, intentional, focused, and hard work on the part of everyone within an organization. While the examples are rooted within schools and school districts, this work is applicable to any organization that seeks meaningful and specific improvement in their results. This is a must-read for leaders!' -Lynn Macan University at Albany - SUNY, Albany, NY.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Educational leadership; School management and organization; School improvement programs; Professional learning communities; Teachers -- In-service training